Functional analysis of natural mutations in two TWIST protein motifs. - Funato, N; Twigg, SR; Higashihori, N; Ohyama, K; Wall, SA; Wilkie, A; Nakamura, M (2005)
The basic helix-loop-helix protein Twist, a transcriptional repressor, is essential for embryogenesis in both invertebrates and vertebrates. Haploinsufficiency of the human TWIST1 gene, which causes the craniosynostosis disorder Saethre-Chotzen syndrome (SCS), is related to failure to repress transcription of CDKN1A (which encodes p21/WAF1/CIP1), promoting osteoblast differentiation. We have examined the functional significance of natural TWIST1 variants present in craniosynostosis patients and in their healthy relatives. Both deletion and duplication variants of the glycine-rich tract Gly5AlaGly5 inhibited E2A (E12/E47)-dependent transcription of CDKN1A to a similar degree as wild-type protein, indicating that the length of this glycine tract is not critical for efficient transcriptional repression. We also evaluated a newly identified heterozygous TWIST1 variant (c.115C>G, encoding p.Arg39Gly), located within a putative nuclear localization signal (NLS), that was present in a child with mild SCS and her clinically unaffected father and grandmother. Unlike wild-type protein, this mutant required cotransfected E12 to localize to the nucleus, indicating that the NLS, including amino acid 39, is essential for nuclear localization; inhibition of E2A-dependent transcription of CDKN1A occurred normally. This analysis further dissects the structure-function relationships of TWIST and corroborates with phenotypic observations of disease expressivity.